2017
DOI: 10.1097/qad.0000000000001589
|View full text |Cite
|
Sign up to set email alerts
|

Oral shedding of herpesviruses in HIV-infected patients with varying degrees of immune status

Abstract: Objective Herpesvirus shedding in the oral cavity was analyzed to determine if presence in the oral compartment correlates with systemic changes in HIV-associated immune deficiency as measured by CD4+ counts, plasma HIV viral load (VL) and presence of AIDS-defining events. Design A5254 is a multicenter, cross-sectional, single-visit study to evaluate oral complications of HIV/AIDS and determine the association between clinical appearance, herpesvirus shedding and immune status as ascertained by CD4 count and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…In this report, we demonstrate that HIV+ EVs from the saliva of HIV-positive patients and culture medium of HIV-infected T cells promote KSHV productive infection in oral epithelial cells cultured in both monolayer and 3-D models, indicating that HIV+ EVs are capable of regulating the initial steps of KSHV infection in the oral cavity. Saliva-mediated oral transmission of KSHV is considered as the most common route for spreading among homosexual people through deep kissing and “mother to child” transmission [3,4,5,6,7,8,9]. Because both saliva and peripheral blood samples [26] from HIV-infected persons contain HIV+ EVs, our findings suggest that the in HIV seropositive people bear higher risk for KSHV infection most likely through EVs in the body fluids.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In this report, we demonstrate that HIV+ EVs from the saliva of HIV-positive patients and culture medium of HIV-infected T cells promote KSHV productive infection in oral epithelial cells cultured in both monolayer and 3-D models, indicating that HIV+ EVs are capable of regulating the initial steps of KSHV infection in the oral cavity. Saliva-mediated oral transmission of KSHV is considered as the most common route for spreading among homosexual people through deep kissing and “mother to child” transmission [3,4,5,6,7,8,9]. Because both saliva and peripheral blood samples [26] from HIV-infected persons contain HIV+ EVs, our findings suggest that the in HIV seropositive people bear higher risk for KSHV infection most likely through EVs in the body fluids.…”
Section: Discussionmentioning
confidence: 87%
“…The oral mucosa is the first target of KSHV infection once the virus is in the oral cavity [6,7,8,9]. To evaluate the initial infection process of oral mucosa by KSHV, we created the 3-dimentional (3-D) organotypic culture by using OKF6/TERT2 cells as described previously [35] (Fig 3A), followed by KSHV infection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, for chronic periodontitis, viruses in the herpesvirus family, which include cytomegalovirus, Epstein‐Barr virus, and herpes simplex virus 1 and 2, have also been detected in periodontal pockets of patients with HIV, and are found in higher numbers compared with patients without HIV . More recent research into the Epstein‐Barr virus has shown it is present in both the chronic and aggressive forms of periodontal diseases, and that they, along with other herpesviruses, are shed into the oral cavity at a greater rate, with more severe immunosuppression …”
Section: Current Investigations Into the Microbiology And The Host Rementioning
confidence: 99%
“…92,93 More recent research into the Epstein-Barr virus has shown it is present in both the chronic and aggressive forms of periodontal diseases, 94,95 and that they, along with other herpesviruses, are shed into the oral cavity at a greater rate, with more severe immunosuppression. 96 Several mechanisms for the direct and indirect role of these viruses in the initiation and pathogenesis of periodontal diseases have been proposed. These include the role of these viruses in promoting the overgrowth of periodontal pathogens and opportunistic infections by suppressing both innate and acquired immunity to pathogenic bacteria, and by directly or indirectly promoting the production and release of a range of inflammatory mediators that result in destruction of the periodontal support.…”
Section: The Virome In the Combined Antiretroviral Therapies Eramentioning
confidence: 99%